Problems And Strategies For Resolving Environmental Issues Of Several Mining Companies In Southeast Sulawesi (Case Study) - Ema Hermawati Garusu; Eka Rahmatia Tuwu; Wa Ode Hastiani Fahidu; La Ode Muhammad Firmansyah; Muhammad Saleh Qadri (International journal of technology and education research, 2025)
Sustainable environmental management is expected to be present not only from the government or environmentalists, but must be applied in real efforts in the field of large industries, which make the environment as the origin of raw materials or raw materials of the company, especially mining companies that have a significant impact on ecological, social and cultural changes from a particular region. Companies in Southeast Sulawesi engaged in mining have many activities and profiles related to environmental issues faced. Various areas that are the point of conservation and cultivation of mining companies have a lot of contact with the environment, be it the natural environment or the artificial environment. In addition, the internal environment of the company also provides many crucial problems for mining companies. The many problems and challenges of the company require that each company must have a powerful resolution strategy for the sustainability of the mining company and the resolution of these environmental issues. This case study aims to identify and describe environmental problems and issues faced and overcome or reconciled by mining companies in Southeast Sulawesi, so as to provide an overview of how to approach sustainable environmental management practically in the field in order to achieve sustainable development goals. This research method is carried out by observation, namely direct observation in the field by conducting documentation, recapitulating secondary data in the form of company files that can be accessed. The results of the case study found that these mining companies manage environmental issues very moderately, where there are work units devoted to addressing environmental issues related to environmental pollution that occurs both physical, chemical and biological. For the work environment, certain work management is applied to overcome Human Resources (HR) problems as well as derivative issues such as work safety (K3), and disaster mitigation. The main strategy of these mining companies is created from solid performance and coordination in increasing environmental awareness without reducing the company's main goal, for sustainable development synergy.